If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 7 = -3 Reorder the terms: 7 + a = -3 Solving 7 + a = -3 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + a = -3 + -7 Combine like terms: 7 + -7 = 0 0 + a = -3 + -7 a = -3 + -7 Combine like terms: -3 + -7 = -10 a = -10 Simplifying a = -10
| 2a+1a=24 | | 5c+6=(3+2c) | | x+19=32 | | z=10+3(x+y) | | 4x-6=3x+2 | | 3(n-1)=1.5(n+2) | | 63=9(2y-3) | | 4(2p-1)=28 | | 2(3+x)=14 | | 8(z+2)-5(z+3)=16 | | -16+x=x-16 | | 4z=7z+12 | | 2(3x-3)+5(x-4)=4(x+2) | | 4(x-3)=2(x-1) | | 23-12x=-(7+2x) | | -1+10=5b-8-4b | | x-4x=-5x-20 | | 56x^2+8x=0 | | 2a^2-9a+3=0 | | 10x^2-26x+12=0 | | 4x^2+8x-77=0 | | 3v^2+28v+49=0 | | x^2=5x+2 | | -3(5t-12)=4t-21 | | 2k^2+3k-14=0 | | 3g^2-7g+2=0 | | 42=6v | | x^2+15x+49=0 | | 8-e=3e+12 | | 6x-(2x-4)=x-(2x-3) | | 2z+0.4=1.2 | | 8x^2-43x-30=0 |